USE OF OIL AND BITUMINOUS ROCKS AND WASTE FROM THEIR PROCESSING IN CREATION OF COMPOSITE SILICATE MATERIALS - T.К. Kuatbayeva,; Zh. Т. Nashiraliyev,; Z. М. Zhambakina,; М. G. Bruyako,; А. Т. Orynova, (Academic Scientific Journal of Chemistry, 2020)
The article considers the issues of technology of silicate materials of dense and cellular structure with usage of oil bituminous rocks and waste from their processing, in particular: the optimization of the ratios of the raw components of a silicate materials mixture, the development of optimal technological parameters for the production of silicate materials, and the technological aspects of the production of the above materials. The optimal compositions of binders with use of waste products from OBR are studied in this work as an activating component of lime or cement. The stability of the samples was studied in various media with a low and high content of basic calcium hydrosilicate. If they contain insoluble silicates and aluminosilicates containing silica, they are acid resistant. Alkali-resistant rocks containing oxides corresponding to strong bases are combined with oxides corresponding to weak acids, for example, calcium and magnesium carbonates. As a result of the experimental work, technological processes for the manufacture of silicate materials (of dense and cellular structure) based on the OBR and waste from their processing are substantiated and developed. The paper reveals the chemical-mineralogical and the structural features of oil bituminous rocks and waste from their processing. The optimal ratio of the waste mixture of oil and bituminous rocks with lime and the technological parameters that ensure the grade of lime-sand binder from 400 to 500 are established. Silicate materials based on this mixture have high physical and mechanical properties and comply with the requirements of the ST standards of the Republic of Kazakhstan for silicate brick and GOST state standard for aerated concrete. Thus, the compositions and conditions for the preparation of these binders with high resistance in large temperature, pressure and aggressive environments are proposed in this work